The Scalar Unparticle Production from the Collision Process in Unparicle Physics - Thuc, Le Nhu; Le Thuy, Dao Thi (VNU Journal of Science: Mathematics - Physics, 2020)
The production of scalar unparticle (spin - 0) in the photon - electron  collider is calculated in all s-, t-, and u-channels in detail as well as interference between channels together. By searching for missing energy distributions as well as evaluating dependence of  differential cross section (DCS) on the scattering angle  and cross section (CS) on the center of mass energy , we hope that the unparticles production in high energy collider might be detected in future.